The ashgate research companion to minimalist and postminimalist music - Gann, Kyle; Potter, Keith; Siôn, Pwyll ap (Surrey Ashgate, 2013)
In recent years the music of minimalist composers has become the subject of important musicological reflection, research and debate. This companion provides an authoritative overview of research in this area and highlights the innovative work of the renowned early minimalists, the distinctive work of second and third generation minimalists, and the work of diverse composers who have moved in parallel with minimalist developments while remaining resolutely outside its immediate environment. The companion also considers minimalism's role in culture and society from the perspective of historiography, analysis, aesthetics and philosophy, and includes interdisciplinary approaches, associations and interconnections.